Comprehensive and rational use of the Caesalpinia spinosa - Caesalpinia tinctoria tare - De la Cruz Lapa, Primo (2004)
The present investigation on the integral and rational use of Tara is the product of an extensive bibliographic review related to this product, in order to know how to use the raw material to obtain tannic acid, widely used in the fur, pharmaceutical, chemistry, paints, etc., and gums for food use from the endosperm, constituting an alternative to traditional gums in the world food, paint and varnish industry, among others; considering that Peru is a country with a varied geography that conditions the heterogeneity of natural resources, the availability and quality of which must be known in order to plan social economic development for the benefit of the rural population.